ANALISIS KINERJA KEUANGAN SEBELUM DAN SESUDAH PENGAWASAN OTORITAS JASA KEUANGAN PADA BANK PERKREDITAN RAKYAT KABUPATEN SEMARANG - Nina Faustina; Rodhiyah Rodhiyah (Universitas Diponegoro, 2017)
Rural Banks (BPR) as one of the banking institutions that closely related to community services need to be fostered and supervised in order to maintain and even improve it’s performance. Since the issuence of Law number 21 in 2011 it established the Financial Services Authority (OJK) to replace the role of Bank Indonesia (BI) in regulating and overseeing the financial sector, especially the banking sector. In terms of number of BPRs have more valuation. This is a great opportunity for financial performance problems and banking crime. So it requires OJK to conduct an integrated supervision with the aim of improving the effectiveness of supervision. The bank's financial performance can be measured using the CAEL ratio, which consists of Capital, Asset, Earning, and Liability categories. The analytical method used is One-Sample Kolmogrov-Smirnov normality test and then using different test Paired Sample t-test for normal distributed data and Wilcoxon Signed Rank Test for non-distributed data. The results of the research with a significance level of 5% showed a difference before and after the supervision on the CAR ratio with the result sig 0,000 <0.05. Therewas no difference before and after surveillance on the NPL ratio with the result of 0.231> 0.05. In earnings ratio there is no difference before and after supervision on BOPO ratio with result sig 0,626> 0,05 and ROA ratio with result of sig 0,372> 0,05. In the ratio of liquidity (liquidity) there is no difference before and after supervision on the ratio of CR with the results sig -0.366> 0.05 and there are differences before and after supervision on the ratio of LDR with the result sig 0.001 <0.05. Conclusions and suggestions: on the CAR and LDR ratios there are significant differences in the period before and after the supervision whereas in the ratio of NPL, BOPO, ROA and CR there is no significant difference in the period before and after the supervision. So it can be said that the switch of bank supervision from BI to OJK did not give effect to the overall change on the financial performance of BPR in Semarang Regency. To realizing better financial performance, OJK supervision should be more intensive and effective in the next period.